1999
DOI: 10.1007/s001250051145
|View full text |Cite
|
Sign up to set email alerts
|

Implications of compound heterozygous insulin receptor mutations in congenital muscle fibre type disproportion myopathy for the receptor kinase activation

Abstract: Recently we reported the association of severe insulin resistance and congenital fibre type disproportion myopathy (CFTDM) in two brothers from a Danish family [1]. It has now been shown that the insulin resistance and possibly the myopathy in the two brothers is associated with compound heterozygous mutations of the insulin receptor gene [2]. The allele inherited from their father, who is less insulin resistant and has no CFTDM [1], has a missense mutation that changes Arg 1174 ®Gln. The allele inherited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
13
1
Order By: Relevance
“…All ten family members affected by hypoglycaemia carried a heterozygous mutation in the IRTK domain of INSR (Arg1174Gln). This mutation has previously been found in three females with the type A syndrome of insulin resistance, and in an apparently healthy male [4][5][6][7]. Complete cosegregation (logarithm of the odds score 3.21) with the disease phenotype supported the proposition that the Arg1174Gln mutation was the cause of hypoglycaemia [3].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…All ten family members affected by hypoglycaemia carried a heterozygous mutation in the IRTK domain of INSR (Arg1174Gln). This mutation has previously been found in three females with the type A syndrome of insulin resistance, and in an apparently healthy male [4][5][6][7]. Complete cosegregation (logarithm of the odds score 3.21) with the disease phenotype supported the proposition that the Arg1174Gln mutation was the cause of hypoglycaemia [3].…”
Section: Introductionmentioning
confidence: 54%
“…Studies of the functional properties of the Arg1174Gln mutation have shown normal insulin binding and affinity to the receptor, but a 70-75% reduction in insulin-stimulated IRTK activity [5][6][7]. Furthermore, in CHO cell lines homozygous for the mutant INSR, stimulation with insulin in the physiological range (1,000 pmol/l) showed a pronounced inability to increase tyrosine phosphorylation of IRS-1, PI3K activity, SLC2A4 translocation and glycogen synthesis [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…For the IR kinase assays, 40 µl lysates (3.5 mg/ml) were added to microwells coated with anti-IR antibody (28) at 4°C. After overnight incubation, the wells were washed, and the kinase activity of immobilized IR was measured in the presence of 0.3 µmol/l ATP containing 3 µCi/well [␥-32 P]ATP and 2.4 µg/ml recombinant IRS-1 as previously described (29). Wells were then washed again, and insulin binding activity (defined as the amount of insulin specifically bound at 8.7 nmol/l) was analyzed as described earlier (28).…”
Section: Subjectsmentioning
confidence: 99%
“…After stimulation with insulin, whole-cell lysates of HEK 293 fibroblasts were added to microwells coated with anti-insulin receptor (aIR) antibody [28]. After the receptor had bound to the antibody, wells were washed and kinase activity was measured in the presence of 0.3 mmol/l [g-32 P]-ATP (3.7±7.4 TBq/mmol) and 2.4 mg/ml recombinant insulin receptor substrate-1 (IRS-1) (Upstate Biotechnology, New York, N. Y., USA) as described previously [29]. Wells were then washed again and insulin binding activity (defined as the amount of insulin specifically bound at 8.7 nmol/l) was analysed as described previously [28] to be sure of similar amounts of insulin receptor.…”
Section: Transient Expression Of Hir-wt Hir-mutants and Substratesmentioning
confidence: 99%